Biodiversidad de ecotipos de Moniliophthora roreri en cacao (Theobroma cacao) clon ccn-51 y la actividad antagonista de PGPR. - Romero Meza, Ricardo Fernando (2018)
The Moniliasis or mal de Quevedo, caused by the fungus M. roreri is the main disease that attacks the fruits of cocoa in Ecuador, its attack is severe which constitutes one of the most important limiting factors in the production of cocoa, in Based on this, it was urgent to study the use of "Plant Growth Promoting Rhizobacteria" (PGPR) as biocontrollers as a viable option in monilla control, if not as promoters in the development of plants without affecting the ecosystem, being friendly to the environment , proposing the present investigation "Biodiversity of ecotypes of Moniliophthora roreri in cocoa (Theobroma cacao) clone CCN-51 and the antagonist activity of PGPR". It was carried out in the Molecular Biology and Microbiology laboratory of the State Technical University of Quevedo, focused on the objectives of obtaining a germplasm bank of M. roreri strains, to characterize the morphological and molecular diversity of the different ecotypes of M. roreri and evaluate the antagonistic activity of PGPR towards the proliferation of the fungus at the in-vitro level. A completely randomized DCA design was applied for the morphological characterization of M. roreri fungus, generating 12 zones to be evaluated. A molecular characterization was carried out by means of ERIC-PCR and ITS generating a phylogenetic tree of the different isolates performing antagonistic tests with bacterial cells and supernatants. After the interpretation and analysis of the results, the following conclusions were obtained: The variability of ecotypes of the fungus M. roreri in Ecuador is closely related to its location in the altitudinal floor and the climatic conditions in which the host crop is found. The favorable conditions for a greater degree of aggressiveness of the fungus M. roreri are an average temperature of 32 oC and a relative humidity of 56% and altitudinal floor of 138 meters above sea level. The supernatants of the bacterial isolates of S. marcescens and P. protegens CHA0 exerted the greatest antagonistic activity in inhibiting the production of M. roreri spores despite their normal mycelial growth. Keywords: PGPR, antagonistic activity, altitudinal floors.